Fashion Design Perception: a Comparative Study of Manual and Digital Methods - Elvera, Resi Sepsilia; Ratri, Pramesti Adika; Nurkholifah, Nurkholifah; Pratiwi, Diah Indah (Yayasan Pendidikan dan Pengembangan Harapan Ananda, 2025)
The fashion industry is undergoing a significant transformation with the integration of digital technology into the design process. This research aims to explore and compare perceptions of fashion designs generated through traditional manual methods and contemporary digital methods. The primary focus is to understand how audiences, both professionals and consumers, assess key aspects such as creativity, innovation, uniqueness, technical quality, and aesthetic appeal of these two design approaches. The proposed research method is a comparative study with a mixed-methods approach (quantitative and qualitative), involving surveys and in-depth interviews with designers, fashion design students, and consumers. The expected results will provide insights into the advantages and disadvantages of each design method from a perceptual perspective, as well as their implications for fashion design practice and education in the digital era. This research is expected to contribute to bridging the gap between traditional design practices and digital innovation, and to provide guidance for designers in choosing the most appropriate approach for their creative goals and target markets.